Methods for the examination of the role of the time factor in managerial and organizational processes - Bácsné Bába, Éva (Acta Agraria Debreceniensis, 2006)
managerial efficiency. The system of investigations is in accordance with the method elaborated and applied by the Department of Management Science of UD, CAS, Faculty of Agricultural Economics and Rural Development (Berde, 2003). This method involves questionnaire interviews and corporate data collection. The first part of the questionnaire contains data with respect to the company, while the second part focuses on the manager being interviewed. The third part is a closed, directed interview-based preference assessment. I aim to assess the sample at my disposal in order to test the research model.In the course of the assessment of questionnaires, I apply descriptive statistical methods for the assessment of the personal and professional features of the managers interviewed and the characteristics of the companies. In the case of questions substantively concerning the time factor – resource, managerial function, reaction time, and impact assessments – I carry out hypothesis testing. I draw up a zero hypothesis, whose appropriateness I test by means of statistical methods. I usually apply rank correlation for the evaluation of the relationship between the variables measured on an ordinal scale in my investigations. This can be applied if not the exact values of the given variables, but only their order in one respect or another is known. If the group building criterion is two-variable Mann-Whimey, if a multi-variable Kruskal-Wallis trial can be applied, which, after the rank transformation, gives information about the acceptance or refusal of the Ho hypothesis through the average of the ranks. The model also contains the managers’ evaluation of the time factor in management work.